The incidence of registry services in the satisfaction of the users of the National Superintendence of Public Registries of Tacna, 2019 - Vargas Romero, Milagros del Rosario (2020)
The objective of this research was to determine the incidence of registry services in the satisfaction of the users of the National Superintendence of Public Registries of Tacna, 2019. Being of a non-experimental basic type, the level of research is analytical. The population is made up of the electoral population of the city of Tacna, with 254,799 inhabitants, with a sample size of 384 users, obtained with a 95% confidence level and a 5% margin of error. The data collection technique is the survey, being as instrument the questionnaire that is validated. The study shows that there is a high correlation between the variables, confirming the positive and significant incidence between the registry services and the satisfaction of the users of the National Superintendence of Public Registries of Tacna.